DEVELOPMENT OF CITYWIDE INCLUSIVE SANITATION (CWIS) METRICS FOR PERCEPTION OF INCLUSIVE SANITATION PERFORMANCE IN THE CITY OF BANDUNG, INDONESIA - Fay'i Safira, Khansa
Access to safe and adequate sanitation is a critical public health and environmental issue, especially in low-income urban areas. The Citywide Inclusive Sanitation (CWIS) approach seeks to address the challenges of achieving universal access to sanitation for all, including the most vulnerable groups. The six main criteria in CWIS are Equity (fairness in the distribution and prioritization of services, service prices, and the use of public finances/subsidies), Safety (safety refers to services that protect customers, workers and the community from safety and health risks due to human waste), Sustainability (to ensure a sustainable system), Responsibility (authorities must carry out a clear mandate to ensure inclusive sanitation services), Accountability (performance is monitored and managed with transparency, data, incentives, and penalties), and Resource Planning and Management (resources are managed to support the implementation of the mandate and achieve goals across time/space). Using a case study of the City of Bandung, this study aims to develop CWIS metrics with a 6-criteria approach. Using six CWIS criteria, this study examines the availability, accessibility, and equitable distribution of sanitation services in the city of Bandung. The study considers inequalities within cities and the potential factors that link them. The metrics that have been developed are tested by Confirmatory Factor Analysis (CFA), the results of the CFA test show that the metrics are consistently constructed. The results of interviews with respondents showed that most of the respondents already had private toilet facilities that used goosenecks, some of the respondents drained their wastewater to septic tanks without routine softeners. Multiple linear regression testing was also carried out to determine the factors that affect CWIS Performance, it is known that the level of Perceived SES and disability conditions affect CWIS Performance. Of the six CWIS criteria, it is known that the lowest score is Resource Planning and Management, and the highest score is the Responsibility criterion.